2019
DOI: 10.1111/ijd.14429
|View full text |Cite
|
Sign up to set email alerts
|

Drug survival of biological therapy is showing class effect: updated results from Slovenian National Registry of psoriasis

Abstract: Background Drug survival is an important measure of successful treatment of patients with chronic diseases such as psoriasis. Therefore, the objective was to calculate drug survival and examine safety profile of biologics and immunomodulators (adalimumab, apremilast, etanercept, ixekizumab, infliximab, secukinumab, and ustekinumab) from the Slovenian National Registry of patients with moderate‐to‐severe psoriasis. Methods Data about the patients with moderate‐to‐severe plaque psoriasis treated with biologics w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
21
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 31 publications
9
21
0
3
Order By: Relevance
“…The results were similar to those previously reported by other studies, with a lower survival in those patients with prior biologic failure, as expected. Lunder et al, based on the national psoriasis registry of Slovenia, also found a similar survival for both anti‐IL‐17 drugs, although it was lower than that achieved by Ustekinumab, suggesting a survival profile common to both, dependent on class. Egeberg et al, based on a national cohort in Denmark, found similar 12‐month survival figures of 84.23% for secukinumab and 87.02% for ixekizumab.…”
Section: Discussionsupporting
confidence: 92%
“…The results were similar to those previously reported by other studies, with a lower survival in those patients with prior biologic failure, as expected. Lunder et al, based on the national psoriasis registry of Slovenia, also found a similar survival for both anti‐IL‐17 drugs, although it was lower than that achieved by Ustekinumab, suggesting a survival profile common to both, dependent on class. Egeberg et al, based on a national cohort in Denmark, found similar 12‐month survival figures of 84.23% for secukinumab and 87.02% for ixekizumab.…”
Section: Discussionsupporting
confidence: 92%
“…In terms of survival analysis, the largest published comparative study is the one conducted with the Slovenian national psoriasis registry, with 613 patients treated with ustekinumab and 98 with ixekizumab 45 . In this study, ustekinumab achieved significantly longer survival rates than the other included drugs, followed by IL‐17 inhibitors (ixekizumab and secukinumab) and anti‐TNF drugs.…”
Section: Discussionmentioning
confidence: 88%
“…difficile) [104][105][106][107]. Доказана более высокая «выживаемость» терапии устекинумабом по сравнению с другими ГИБП (ингибиторы ФНОα и ИЛ17, ведолизумаб) у пациентов с Пс и ПсА, ВЗК [108][109][110][111][112][113][114][115][116]. Раннее ингибирование ИЛ23 устекинумабом способствует уменьшению субклинических воспалительных изменений в энтезисах у пациентов с Пс в течение 12 нед терапии, при этом данный эффект сохраняется и к 52-й неделе лечения [117].…”
Section: раннее назначение гибпunclassified